Mouth Rinsing With a Pink Non-caloric, Artificially-Sweetened Solution Improves Self-Paced Running Performance and Feelings of Pleasure in Habitually Active Individuals - Brown, Daniel R.; Cappozzo, Francesca; De Roeck, Dakota; Zariwala, Mohammed Gulrez; Deb, Sanjoy K. (Frontiers in Nutrition, 2021)
Purpose: The purpose of this study was to investigate whether mouth rinsing with a pink non-caloric, artificially sweetened solution can improve self-selected running speed and distance covered during a 30 min running protocol. Methods: Ten healthy and habitually active individuals (six males, four females) completed two experimental trials in a randomised, single-blind, crossover design. Each experimental trial consisted of a 30 min treadmill run at a self-selected speed equivalent to 15 (hard/heavy) on the rating of perceived exertion scale. During exercise, participants mouth rinsed with either a pink or a clear non-caloric, artificially sweetened solution, with performance, perceptual and physiological measures obtained throughout. Results: Self-selected running speed (+0.4 ± 0.5 km·h−1, p = 0.024, g = 0.25) and distance covered (+213 ± 247 m, p = 0.023, g = 0.25) during the 30 min running protocol were both improved by 4.4 ± 5.1% when participants mouth rinsed with the pink solution when compared to the clear solution. Feelings of pleasure were also enhanced during the 30 min treadmill run when participants mouth rinsed with the pink solution, with ratings increased from 3.4 ± 0.7 in the clear condition to 3.8 ± 0.6 in the pink condition (+0.4 ± 0.5, p = 0.046, g = 0.54). Conclusion: Mouth rinsing with a pink non-caloric, artificially sweetened solution improved self-selected running speed, total distance covered, and feelings of pleasure obtained during a 30 min running protocol when compared to an isocaloric and taste-matched clear solution.